Análise imuno-histoquímica da expressão das proteínas KIT, BRAFV600E, CICLINA D1, PTEN e MYC em melanoma extensivo superficial in situ e fino (≤ 1 mm de espessura) - Germano, Andressa [UNIFESP] (2016)
Cutaneous melanoma (CM) is a malignant tumor arising from the uncontrolled proliferation of melanocytes. Although it represents only 3% to 5% of skin neoplasia,it accounts for 65% of deaths from cutaneous neoplasia. In previous results, our research group showed that melanoma, above 1 mm thick, had heterogeneous expression of SCF, KIT, BRAF, CYCLIN D1, MYC and PTEN. The evaluation by sequencing of BRAF and KIT confirmed the results of protein expression. However, thin melanomas and in situ melanomas were constituted in gap in this research,which is the reason of this study. Objectives: To evaluate the immunohistochemical expression of KIT proteins, BRAF V600E,CYCLIN D1, MYC and PTEN in thin melanomas (?1mm) and in situ melanomas and correlate the expression of these markers by immunohistochemistry. Material and Methods: 50 samples were selected from private service. Samples were studied by immunohistochemistry and evaluated by semi-quantitative method, thus establishing positive scores through the sum of percentage scores of stained cells, and intensity of staining. Results: Out of the 15 in situ melanomas and 35 thin melanomas, after review of the samples, a total of 10 (ten) in situ melanomas and thirty-five thin melanomas were left for the study. The expression of the markers thin and in situ melanomas obtained positivity for KIT in 70,45% of cases, BRAFV600E in 50%, Cyclin D1 in 41,86%, PTEN in 28,57%, and MYC in 4,54%.of the samples. There was a statistically significant association of immunohistochemistry expression between KIT and BRAFV600E markers. Conclusion: There was association of BRAFV600E expression with KIT in thin melanomas